INCLUSIVE LEADERSHIP TO BUILD AN INCLUSIVE CAMPUS - Umi Zulfa (PROCEEDING AL GHAZALI International Conference, 2023)
This research is motivated by concerns over leadership practices that tend not to be inclusive, and tend to discriminate against certain groups, which leads to unfavorable organizational situations and poor performance. Therefore, the research aims to determine inclusive leadership behavior among middle-level leadership at UNUGHA Cilacap. This research uses data collection methods in the form of questionnaires, observations, and interviews and the data is analyzed using descriptive statistics and confirmed with data from observations and interviews. This research indicates that inclusive leadership behavior among middle-level leaders at UNUGHA Cilacap is high. Inclusive leadership practices backed up by the inclusiveness of the institution's Core Values give birth to a conceptual model of an Inclusive Campus Based on Core Values for a more dignified campus.